0889 Sleep Determinants of Incident Hypertension in a Population-Based Cohort: The CoLaus-HypnoLaus Study. (27th April 2018) - Heinzer, R; Hirotsu, C; Marques-Vidal, P; Vollenweider, P; Waeber, G; Tafti, M; Betta, M; Bernardi, G; Siclari, F; Haba-Rubio, J
Abstract: Introduction: An association between sleep-disordered breathing and cardiovascular risk factors such as hypertension has been suggested. Potential mechanisms underlying this association include sleep fragmentation, intermittent hypoxia and autonomic activations. The aim of this study was to analyze the sleep determinants of incident hypertension in a population-based cohort. Methods: CoLaus is a prospective population-based cohort in which cardiovascular profile was assessed at baseline and 2 subsequent follow-ups. Hypertension was defined as systolic blood pressure (SBP) ≥140 mm Hg, diastolic blood pressure (DBP) ≥90 mm Hg, or antihypertensive drug use. HypnoLaus study analyzed sleep characteristics in a subset of CoLaus population at the first follow-up (6.4 ± 0.2 years after baseline). All HypnoLaus participants underwent a full polysomnography (PSG) at home. The apnea/hypopnea index (AHI) was determined according to the recommended AASM-2012 criteria. The autonomic activation during sleep was assessed using pulse wave amplitude (PWA) drops based on the photoplethysomnographic signal of PSG. Results: Of the 1304 participants (mean age 49.1 ± 9.6 y.o., 56% women) without hypertension at baseline, 338 (25.5%, mean age 51.6 ± 16.8 y.o., 51% women) developed hypertension at the second follow-up (10.8 ± 0.1 years interval). After adjustment for age, sex, BMI, delta BMI (between baseline and PSG), baseline SBP and DBP, the following sleep parameters were independently associated with incident hypertension: PWA drops duration (OR for 1 second: 1.10 [1.04–1.16], p=0.001), AHI in REM sleep (OR for 1 event/h: 1.02 [1.01–1.03], p=0.001), and %time spent with an oxygen saturation <90% (OR for 1%: 1.01 [1.00–1.03], p=0.042). In a stepwise multivariate logistic regression including all significant parameters in bivariate analysis, PWA drop duration (p=0.0001) and REM-AHI (p=0.003) were the only sleep parameters that remained associated with incident hypertension. Conclusion: Nocturnal autonomic activation and AHI during REM sleep seem to contribute to incident hypertension in the middle-to-older-age CoLaus-HypnoLaus cohort. Support (If Any): Faculty of Biology and Medicine of Lausanne, the Swiss National Science Foundation (grants 3200B0-105993, 3200B0-118308, 33CSCO-122661, 33CS30-139468 and 33CS30-148401), Leenaards Foundation, and Vaud Pulmonary League (Ligue Pulmonaire Vaudoise).